A Novel 7H‑[1,2,4]Triazolo[3,4‑b]thiadiazine-based Cystic Fibrosis Transmembrane Conductance Regulator Potentiator Directed toward Treatment of Cystic Fibrosis - Rab, Andras; Yang, Xun; Tracy, William F.; Hong, Jeong S.; Joshi, Disha; Manfredi, Candela; Ponnaluri, Sadhana S.; Kolykhalov, Alexander A.; Qui, Min; Fu, Haian; Du, Yuhong; Davies, Huw M. L.; et al. (ACS medicinal chemistry letters, 2023)
Cystic fibrosis (CF) is an autosomal genetic disorder caused by disrupted anion transport in epithelial cells lining tissues in the human airways and digestive system. While cystic fibrosis transmembrane conductance regulator (CFTR) modulator compounds have provided transformative improvement in CF respiratory function, certain patients exhibit marginal clinical benefit or detrimental effects or have a form of the disease not approved or unlikely to respond using CFTR modulation. We tested hit compounds from a 300,000-drug screen for their ability to augment CFTR transepithelial transport alone or in combination with the FDA-approved CFTR potentiator ivacaftor (VX-770). A subsequent SAR campaign led us to a class of 7H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazines that in combination with VX-770 rescued function of G551D mutant CFTR channels to approximately 400% above the activity of VX-770 alone and to nearly wild-type CFTR levels in the same Fischer rat thyroid model system.